P-BN42 Percutaneous cholecystostomy - A practice review. (16th December 2021) - Li, Wing Ching; Elboraey, Omar; Kilani, Mohammad Saeed; Pursnani, Kishore Gopaldas; Rajendran, Ilayaraja
Abstract: Background: Percutaneous cholecystostomy (PC) is performed occasionally in a highly selected group of patients with variable outcomes. The World Society of Emergency Surgery (WSES) updated guidelines(2020) has recommended PC as a treatment modality in patients admitted with 'acute calculous cholecystitis'(ACC) with who are not fit for surgery, including septic patients and those who show no improvement on conservative management within 48 hours. An audit was organised to review our patient selection for PC in the last 5 years in comparison to the latest WSES recommendations. Methods: A retrospective observational study was conducted using a prospectively collected hospital database on patients who underwent PC between March 2016 and March 2021 in a teaching hospital. The patient cohort who underwent PC were compared and analysed against the set WSES guidelines. Results: Some 23 patients were included. The median age was 82 years (range-61-90), with 13 females (56.5%) and 10 males (43.5%).19/23(82.6%) patients were at risk of sepsis on presentation, with two or more amber flag symptoms, whereas 4/23(17.4%) patients presented with confirmed sepsis. 19/23 (82.6%) were deemed unfit for surgery against 4/23 who were deemed fit based on the surgeons assessment. Patients unfit for surgery were treated with antibiotics following a diagnosis of ACC. The median time for patients to undergo PC from admission was 4 days. The 30-day mortality rate was 13 % (n = 3/23). Conclusions: The study has demonstrated that our current practice for managing patients admitted with ACC and performing PC are mostly in line with the WSES guidelines. Considering individuals presentation and the surgeons clinical judgement into account, the practice was also likely impacted by COVID-19 the global pandemic. Further clinical studies may be required to determine specific patient groups who would benefit from PC.